Dispositional Predictors of Students' Conflict Resilience - Lepekhin, N.N.; Kruglov, V.G.; Kruglova, M.A.; Tikhomirova, N.V.; Iashina, M.A. (Socialʹnaâ Psihologiâ i Obŝestvo, 2023)
Objective. The study of dispositional predictors of students' conflict resilience.Background. Against the background of the consequences of self-isolation and the limitations of real communication, it is relevant to study resilience to conflicts as an important communicative and professional characteristic of social self-determination. The study of dispositional predictors of conflict resilience allows creating scientifically based programs for its formation among students.Study design. The influence of the severity of stress, aggression, empathy, assertiveness and other independent variables on conflict resilience, considered as a dependent variable, was studied. Statistical hypotheses were verified by means of factor analysis and structural equation modeling (SEM).Participants. The sample consisted of students of the natural sciences and humanities faculties of St. Petersburg State University in the number of 205 people, 49 of them men (24%) and 156 women (76%), aged 17 to 27 years, the median value is 19 years.Methods (tools). Questionnaire Determination of the level of conflict resilience (N.P. Fetiskin, V.V. Kozlov, G.M. Manuilov); Personality assertiveness test (V.P. Sheinov); PSM-25 psychological stress scale, in adaptation by Vodopyanova N.E.; diagnostic questionnaire for empathy A. Mehrabian, N. Epstein; diagnostic questionnaire for indicators and forms of aggression A. Bass, A. Darkey.Results. Because of confirmatory factor analysis, the variables stress, hostility, irritation were combined into the factor "paranoia" (suspicion, suspiciousness, resentment, stress and irritability). The variables verbal, physical, indirect types of aggression and negativism are combined into the factor "aggressiveness" (contradiction to the norms of society and the focus on causing harm to others). The variables empathy, assertiveness (-), guilt are combined into the "tolerance" factor (empathy, the desire to understand the reasons for the behavior of another, compliance and auto-aggression due to regular sacrifice of one's own interests). The joint influence of these factors on conflict resistance was revealed, the total variance is 55%. "Paranoia" and "aggression" reduce conflict resilience and promote conflict striving, "tolerance" enhances conflict resilience, but at high values, causes conflict avoidance.Conclusions. Psychological dispositions that affect conflict resilience can be combined into three factors: paranoia, aggression, tolerance, which have a multidirectional effect. Paranoia and aggression promote conflict-seeking behavior and reduce conflict resilience. Tolerance increases conflict resilience, but contributes to conflict avoidance. This conflict resilience dynamics can be described by an inverted V-shaped curve, which shows that conflict resilience arises because of a balance of the identified factors. Цель. Изучение диспозиционных предикторов конфликтоустойчивости студентов.Контекст и актуальность. На фоне последствий самоизоляции и ограничений реального общения актуальным является исследование устойчивости к конфликтам как характеристики социального самоопределения. Изучение диспозиционных предикторов конфликтоустойчивости позволяет создать научно обоснованные программы по ее формированию у студентов.Дизайн исследования. Было изучено влияние выраженности стресса, агрессии, эмпатии, ассертивности на конфликтоустойчивость студентов. Проверка статистических гипотез осуществлялась посредством конфирматорного факторного анализа и метода моделирования структурными уравнениями (SEM).Участники. Выборку составили студенты естественных и гуманитарных факультетов СПбГУ в количестве 205 человек: 156 девушек (76%) и 49 юношей (24%) в возрасте от 17 до 27 лет, медиана - 19 лет.Методы (инструменты). Тест ассертивности личности (В.П. Шейнов); Шкала психологического стресса PSM-25 (Н.Е. Водопьянова); Опросник диагностики эмпатии (А. Мехрабиен, Н. Эпштейн); Методика диагностики показателей и форм агрессии (А. Басс, А. Дарки); Тест определения уровня конфликтоустойчивости (Н.П. Фетискин и др.).Результаты. В результате факторного анализа переменные «стресс», «враждебность», «раздражение» были объединены в фактор «паранойяльность» (подозрительность, мнительность, обидчивость, стресс и раздражительность). Переменные «вербальная агрессия», «физическая агрессия», «косвенная агрессия» и «негативизм» объединены в фактор «агрессия» (противоречие нормам общества и направленность на причинение вреда окружающим). Переменные «эмпатия», «ассертивность» (-), «вина» объединены в фактор «терпимость» (сопереживание, стремление понять причины поведения другого, уступчивость и аутоагрессия из-за регулярного жертвования собственными интересами). Выявлено совместное влияние данных факторов на конфликтоустойчивость, суммарная дисперсия - 55%. «Паранойяльность» и «агрессия» снижают конфликтоустойчивость и способствуют конфликтостремлению, «терпимость» усиливает конфликтоустойчивость, но при высоких значениях вызывает конфликтоизбегание.Основные выводы. Психологические диспозиции, влияющие на конфликтоустойчивость, могут быть объединены в три фактора: «паранойяльность», «агрессия», «терпимость», оказывающие разнонаправленное влияние. «Паранойяльность» и «агрессия» способствуют поведению конфликтостремления и снижают конфликтоустойчивость. «Терпимость» повышает конфликтоустойчивость, но способствует конфликтоизбеганию. Динамика конфликтоустойчивости может быть описана инвертированной V-образной кривой, которая показывает, что конфликтоустойчивость возникает в результате баланса выделенных факторов.